2022
DOI: 10.3390/bios12100868
|View full text |Cite
|
Sign up to set email alerts
|

Generation of Dynamic Concentration Profile Using A Microfluidic Device Integrating Pneumatic Microvalves

Abstract: Generating and maintaining the concentration dilutions of diffusible molecules in microchannels is critical for high-throughput chemical and biological analysis. Conventional serial network microfluidic technologies can generate high orders of arbitrary concentrations by a predefined microchannel network. However, a previous design requires a large occupancy area and is unable to dynamically generate different profiles in the same chip, limiting its applications. This study developed a microfluidic device enab… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 67 publications
0
7
0
Order By: Relevance
“…However, measurement of the deformation is challenging and mainly by either numerical simulation or imaging. For instance, simulation revealed that 2000 mbar was necessary to deflect a 20 μm thick film (with a curing ratio of 10:1) for by 30 μm [ 56 , 57 ]. The confocal microscopy has been employed for a more intuitive visualization of membrane deformation [ 48 ].…”
Section: Resultsmentioning
confidence: 99%
“…However, measurement of the deformation is challenging and mainly by either numerical simulation or imaging. For instance, simulation revealed that 2000 mbar was necessary to deflect a 20 μm thick film (with a curing ratio of 10:1) for by 30 μm [ 56 , 57 ]. The confocal microscopy has been employed for a more intuitive visualization of membrane deformation [ 48 ].…”
Section: Resultsmentioning
confidence: 99%
“…Soft lithography is frequently used to fabricate microdevices such as pneumatic micropumps 51,59–62 and microvalves. 52,57,63,64 This fabrication technique has also been used for hydraulically actuated microdevices. 55 Ni et al 111 reported an electromagnetic actuator with liquid metal embedded in the microfluidic structures.…”
Section: Fabrication Methods For Actuators and Flexible Microdevicesmentioning
confidence: 99%
“…Furthermore, the flexible structure not only serves as a valve to fully close a microchannel in microvalves but also acts as a regulator by partially closing the microchannel to tune its fluidic resistance. 64…”
Section: Actuation Principlesmentioning
confidence: 99%
See 1 more Smart Citation
“…Generating the concentration dilutions of diffusible molecules in microfluidic devices is important for high-throughput biochemical analysis. Chen et al [22] reported a microfluidic device integrated with programmable pneumatic microvalves for adjusting both the concentration in a single channel and the concentration distributions in different channels. They systematically studied the performance of the pneumatic microvalves via experiments and numerical simulations.…”
mentioning
confidence: 99%